PROFESSIONAL SATISFACTION IN DENTISTRY - SOCIO-DEMOGRAPHIC PROFILE OF DENTISTS IN BULGARIA - Avramova, Nadya; Mihaylova, Ivanka (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Aim: To investigate the influence of some socio-demographic determinants – age, gender, location and ownership of dental practice – on professional satisfaction among dentists in Bulgaria. Method and Materials: A self-administrated questionnaire consisting of 37 items about sociodemographic characteristics, motivation, work environment and economic factors was mailed to a random sample of 1427 dentists from 107 settlements in Bulgaria (response rate=30.5%, n=436). Results: Dentists aged 36-45 were found to be completely satisfied – 104(35.9%), p<0.05. It was not found statistically significant association between professional satisfaction and gender of the respondents (p=0.265). There was also statistically significant association between dentist’s job satisfaction and location and ownership of dental practice (p-value<0.05). Conclusion: Socio-demographic profile of the most satisfied dentist in Bulgaria was associated to 36-45 aged practitioner, regardless of gender, working in big city and owning his/her dental office.